Perioperative anesthetic management in pediatric with pheochromocytoma tumor resection - Thius, Adi Dharma; Kurniyanta, Putu; Putra, Kadek Agus Heryana; Sinardja, I Ketut (DiscoverSys Inc., 2019)
Pheochromocytomas (PCC) is rare neuroendocrine tumors which present as the malignant and familial features. These catecholamine-secreting tumors have triad classical symptoms of headache, sweating, and palpitation primarily due to the release of catecholamines and their metabolites in the body with hypertensive crisis become its predominant clinical symptoms. The excessive release of catecholamines may produce a life-threatening hemodynamic surge during the intraoperativeperiod, therefore preoperative preparation and intraoperative monitoring become an essential point. Nevertheless, postoperative care is also a critical issue in order to further curtail its morbidity and mortality rates.